Project evaluation - Corrie, R. K. (Engineering management., 1991)
This clear, straightforward book is concerned with the evaluation of an engineering project and factors which affect its outcome at any stage in its life-cycle. It deals with the initial project feasibility appraisal and the subsequent review of performance which ensures the project`s objectives are met.